The Allergic Rhinitis Clinical Investigator Collaborative (AR‐CIC): verification of nasal allergen challenge procedures in a study utilizing an investigational immunotherapy for cat allergy. Issue 1 (12th April 2018) - Neighbour, Helen; Soliman, Mena; Steacy, Lisa M.; Hickey, Pascal; Forbes, Beth; Larché, Mark; Ellis, Anne K.
Abstract: Background: The Allergic Rhinitis Clinical Investigator Collaborative (AR‐CIC) is a network of experienced Allergic Rhinitis (AR) researchers developing better research tools based on the nasal allergen challenge (NAC). A key objective of such is the ability to detect efficacy in a small population. AR‐CIC sought to test its NAC protocol as a secondary objective in two small mechanistic research trials of a novel form of immunotherapy [Cat Peptide Antigen Desensitisation (Cat‐PAD)] for which efficacy had previously been demonstrated. The primary objective (not presented here) was to identify potential biomarkers of efficacy for peptide immunotherapy, and this provided an ideal opportunity to corroborate the NAC protocol. We aim to clinically validate the AR‐CIC NAC methodology in a pooled analysis of secondary endpoints measured in two open label mechanistic studies of cat allergic participants treated with Cat‐PAD. Methods: Cat allergic AR sufferers with ongoing cat exposure were included. Participants had to demonstrate a total nasal symptom score (TNSS) of at least 8 (max 12) and/or achieve a reduction in peak nasal inspiratory flow (PNIF) of ≥ 50% during a screening titrated NAC. Eligible participants then underwent a baseline NAC visit with the allergen dose that produced a positive challenge at screening, followed by four monthly injections of 6 nmol Cat‐PAD. A follow up NAC visit documented changes in nasal response 1 month following the completion of treatment. Results: Nineteen subjects completed the study protocol in the two studies combined. Four injections of Cat‐PAD resulted in a significant reduction in TNSS responses generated via NAC following allergen challenge (15 min p  < 0.05, 30 min p  < 0.05, 1 h p  < 0.01, 2 h p  < 0.05). There was modest correlation between symptom scores and PNIF measurements. Conclusions: This study supports the validity of the AR‐CIC's optimised NAC protocol for conducting research of the potential efficacy of novel therapeutics in multi‐centre studies. Trial registration Both studies reported herein were registered clinicaltrials.gov (NCT01383590 and NCT01383603)